Performance enhancement of OCDMA system based on sequential algorithm (SeQ) Code - C. A. S. Fazlina; C. B. M. Rashidi; S. N. Azemi; S. A. Aljunid; S. Yaakob (Institute of Advanced Engineering and Science, 2019)
This paper presents a new class of Sequential Algorithm (SeQ) code for Optical Code Division Multiple Access (OCDMA) system. The SeQ code has advantages of various cross – correlation property at any given number of users, and code weights. The result shown, at error floor BER = 10-09, the SeQ code capability to support 190 numbers of simultaneous users was higher than those achieved by FCC (W=4), DCS (W=4) and MFH (W=4). SeQ code excellently support 190 number of users due to due to the arrangement of code algorithm and flexibility cross-correlation (0 and 1) role. In addition, SeQ code capable to support up to 70 km for bit rate 155 Mbps in comparison 622 Mbps, 1 Gbps, and 2 Gbps be able to support 40km, 30km and 20km respectively. Hence, we can ascertain that PIIN and MAI are successfully eliminated for SAC-OCDMA coding system.